1994
DOI: 10.1002/j.1551-8833.1994.tb06247.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of arsenic removal during coagulation and Fe–Mn oxidation

Abstract: Recent studies have indicated that arsenic in drinking water is as hazardous as radon in homes and secondhand tobacco smoke. Arsenic removal during coagulation or Fe–Mn oxidation is examined to aid utilities that desire to improve arsenic removal. Fundamental mechanisms of arsenic removal are discussed, optimization strategies are forwarded, and some new insights are provided to guide future research. Specifically, As(III) removals by coagulation are primarily controlled by coagulant dose and relatively unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
1
8

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(173 citation statements)
references
References 33 publications
3
161
1
8
Order By: Relevance
“…Ferric chloride (FeCl 3 ) was used as a coagulant. The chemical coagulation experiments were conducted using jar test apparatus as specified in the literature (Edwards, 1994;Hering et al, 1996). The summary of experimental conditions employed is presented in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferric chloride (FeCl 3 ) was used as a coagulant. The chemical coagulation experiments were conducted using jar test apparatus as specified in the literature (Edwards, 1994;Hering et al, 1996). The summary of experimental conditions employed is presented in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…The commonly used technologies include coagulation and precipitation with iron and aluminum salts (Edwards, 1994;Hering et al, 1996), adsorption onto activated alumina, activated carbon and activated bauxite (Gupta and Chen, 1978), ion exchange and reverse osmosis (Clifford, 1999). Some recent treatment technologies based on oxidation and adsorption are green sand filtration (Christen, 2000), iron oxide coated sand (Joshi and Chaudhuri, 1996), manganese dioxide coated sand (Bajpai and Chaudhuri, 1999), ferruginous manganese ore (Chakravarty et al, 2002), ferrihydrite (Jain et al, 1999), clay minerals (Manning and Goldberg, 1997) and zero-valent iron (Fendorf et al, 1997;Farrell et al, 2001;Su and Puls, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies by other researchers have indicated that precipitation of Fe-As and Mn-As phases is very unlikely. The introduction of ferric ions for removal of arsenic from hydrometallurgical processed solutions and in water treatment has been studied by many researchers (Robins et al, 1987;Edwards, 1994;Cheng et al, 1994;Hering et al, 1996). These studies indicated that coagulation and adsorption are the major mechanisms for arsenic removal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ferric ion has been used as an effective coagulation reagent in the treatment of arseniccontaminated wastewater (Cheng et al, 1994;Edwards, 1994;Hering et al, 1996). A study by Krause and Ettel (1988) showed that arsenic can form relatively insoluble ferric iron compounds, which have solubility products on the order of 10−20 to 10−24.…”
Section: In Situ Chemical Fixation Batch Experimentsmentioning
confidence: 99%